2001
DOI: 10.1074/jbc.m104320200
|View full text |Cite
|
Sign up to set email alerts
|

An Isoform of Branched-chain Aminotransferase Is a Novel Co-repressor for Thyroid Hormone Nuclear Receptors

Abstract: The functions of thyroid hormone receptors (TRs) are regulated by a host of co-regulatory proteins. Tissue-specific expression of these co-regulators leads to distinct expression patterns and regulation of thyroid hormone (T3) target genes in tissues. Previously we have found that human colon carcinoma RKO cells exhibit strong T3-independent transcriptional activity. We therefore searched for co-regulatory proteins in RKO cells using a yeast two-hybrid system with the intact TR␤1 as bait. One of the three posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Two other variants have also been described that are homologous to hBCATm: a novel alternatively spliced variant found in placental tissue and a splice variant that is reported to act as a co‐repressor of thyroid hormone nuclear receptors (Lin et al . ; Than et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Two other variants have also been described that are homologous to hBCATm: a novel alternatively spliced variant found in placental tissue and a splice variant that is reported to act as a co‐repressor of thyroid hormone nuclear receptors (Lin et al . ; Than et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has shown that a splice variant of BCATm with an internal deletion of 12 amino acids is expressed in colon carcinoma cells (41). This isoform of BCATm binds to the thyroid hormone receptor and enhances its effects on nuclear transcription activity (41). Furthermore, BCATm has a redox-active CXXC center (9) and has been found to associate with BCKD and other proteins (27).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that, for both BCATm and BCATc, nonenzymatic roles in intracellular signaling may be possible. Recent work has shown that a splice variant of BCATm with an internal deletion of 12 amino acids is expressed in colon carcinoma cells (41). This isoform of BCATm binds to the thyroid hormone receptor and enhances its effects on nuclear transcription activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of MalY in the transduction of an unknown signal to MalT remains to be established. Finally, a short isoform of the human branched chain aminotransferase is also a co-repressor for thyroid hormone receptor-mediated transcription by a physical interaction between these two proteins (42).…”
Section: Discussionmentioning
confidence: 99%